Estudo de sinais de matrizes multieletrodo (MEAs) em termos do janelamento - Cardoso, Rodrigo Ribeiro (2010)
This work studies a segmentation tool for application to multielectrode arrays (MEAs) signals. Studies of neuronal cultures signals by means of MEA have opened a wide research field. However, classical tools for analyzing these kinds of signals have focused on spikes detection and on time series intervals between spikes (ISI). The search for new tools on signal analysis and segmentation can boost investigations and their applications. There is opportunity for classical mathematical tools such as autocorrelation yet. Results and discussions on application of this technique in multielectrode array signals are presented. The application of this tool in cellular inactivity identification has great potential. An algorithm applying the segmentation technique by SEM (Spectral Error Measurement) is also presented. The results are not conclusive; however, new possibilities are opened for future investigation on this technique and others techniques of signals segmentation for applying on MEA signals. Finally, comparative applications of the developed tools in electroencephalographic signals (EEG) are presented.